Kepemilikan keluarga sebagai determinan kinerja perusahaan dengan biaya keagenan sebagai moderasi - Saputra, Bayu Swastika; Muazaroh, Muazaroh; Suhartono, Suhartono (Universitas Hayam Wuruk Perbanas, 2022)
Family ownership still dominates the companies’ ownership structure in Indonesia. However, family ownership can also have a positive or negative impact on the company’s performance the previous studies related to the impact of family ownership on the company’s performance provides different results. The purpose of the study was to examine the family ownership as determinant of the company’s performance with agency cost as a moderating variable. It took the sample of 13 manufacturing companies in the industrial and consumption sectors listed on the Indonesia Stock Exchange for the 2017-2020 periods. They were taken using a purposive sampling method. The data were analyzed using multiple linear regressions. The results showed that family ownership has a positive effect on the company’s performance, which means the greater the percentage of family ownership, the better the company's performance. It also showed that agency cost did not moderate the effect of family ownership on company performance. It can be implied that family ownership has a strong motivation to supervise company management to improve company performance.